REGULASI DIRI SISWA SEKOLAH KHUSUS OLAHRAGA RAGUNAN BINAAN PEMERINTAH PROVINSI DKI JAKARTA - Novendawati Wahyu Sitasari; Wara Rahmawati; Yuli Asmi Rozali (MOTORIC, 2019)
The purpose of this study was to find out how self-regulation of SKO Ragunan students. The population and sample from this study amounted to 222 SKO Ragunan Fostered DKI Jakarta Provincial Government consisting of 115 male students and 107 female students. This research belongs to the type of quantitative research that is descriptive in nature. Data is collected by distributing self-regulation questionnaires based on the theory of Omrod (2009). Data analysis is done by making a total score category of self-regulation. The results showed that students of SKO Ragunan Fostered by the DKI Provincial Government who had medium regulation were 86.5% more than those who had high regulation of 13.5%. Besides male students have more good regulation than female students. And students with team or team sports have higher regulations than students from individual sports